Perancangan User Experience Alat Ukur Evaluasi Pengalaman Pengguna Metode Intrinsic Motivation Inventory berbasis Website (Studi Kasus : Diskominfo Ngawi) - Annisa Sukmawati; Mahardeka Tri Ananta; Dwija Wisnu Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
User experience is all the effects felt by the user after the user interacts with the system, device, or product. User experience is one of the most important things to consider, both during the design and development process of a product. The goal is to find out how users feel, assess motivation and find out user expectations for the system. Intrinsic Motivation Inventory (IMI) is one of the methods used to measure the subjective experience of users who interact with the system. Evaluation in this method prioritizes the level of intrinsic user perceptions of the value/usefulness scale, interest/enjoyment, and the perception of user choice when interacting with the system. To follow up on these problems, researchers provide a design solution in the form of an IMI-based measuring instrument called IMITO. In designing IMITO, researchers chose the User Centered Design (UCD) method, because the method design process focuses on the user's needs and a more in-depth analysis of the target audience. Evaluation of design solutions in accordance with usability testing tested by 12 participants. The results of the usability test on the effectiveness aspect are 98%, the efficiency aspect is 13.44 goals/second and the satisfaction aspect is 75% which is included in grade B. Based on these three aspects, the final usability score is 90.02% which is included in the adjective rating category Excellent, grade A.